Male immune infertility: criteria for differential diagnosis - V. A. Bozhedomov; N. A. Lipatova; R. A. Kamarina; A. V. Bozhedomova; I. A. Korneev; A. A. Kamalov (Вестник урологии, 2025)
Introduction. Autoimmune reactions against spermatozoa represent a recognized cause of male infertility. The presence of antisperm antibodies (ASAs) can lead to reduced sperm motility, impaired capacitation and acrosome reaction, as well as increased sperm DNA fragmentation. However, current WHO guidelines do not establish definitive diagnostic criteria for «male immune infertility.» Instead, they recommend developing regional reference ranges based on the 5th to 95th percentile values derived from fertile men populations.Objective. To establish reference ranges for the percentage of ASAs-IgG-positive spermatozoa in fertile Russian men in order to enhance the clinical and economic effectiveness of infertility management in couples.Materials & Methods. The study is an observational, multicenter, cross-sectional, retrospective analysis. Antisperm antibodies (ASAT) on spermatozoa were assessed using the mixed antiglobulin reaction (“MAR-IgG”) method recommended by the WHO (“FertiPro”, Beernem, Belgium). A cohort of fertile men (n = 358) was selected based on the following criteria: 1) their partners achieved pregnancy (hCG > 100 mIU/ml and/or ultrasound confirmation of a gestational sac) occurring naturally within 12 months after discontinuation of contraception, with the semen analysis performed within 3 months of conception at a specialized andrology laboratory; 2) absence of any specific treatment for at least 3 months prior to the date of conception. Two subgroups were identified: subgroup 1 (n = 255), in which semen volume, concentration, motility, and morphology met the WHO 2021 reference ranges; and subgroup 2 (n = 337), in which these parameters corresponded to Russian regional reference criteria (Bozhedomov et al., 2023).Results. In the cohort of fertile men (n = 358), MAR-IgG test results ranged from 0 to 100%, with a median of 0% and the 5th to 95th percentiles spanning 0% to 40%. MAR-IgG levels exceeding 40% were observed in 4.5% of cases (16 out of 358). Within subgroup 1, all instances of MAR-IgG > 10% were identified as statistical outliers based on the standard English “non-outlier range,” with the 95th percentile at 36%. According to the Russian reference criteria, MAR-IgG values above 12% and the 95th percentile of 40% were considered outliers. No statistically significant differences were found between subgroups 1 and 2 regarding distribution patterns and frequency of cases exceeding these thresholds (p > 0.05).Conclusion. In Russian men, the proportion of IgG-positive progressively motile spermatozoa should not exceed 12%. When this proportion ranges from 13% to 40%, an immune-mediated contribution to infertility is considered probable. Pregnancy is statistically unlikely when more than 40% of progressively motile spermatozoa are IgG-positive, even in the presence of normozoospermia, indicating a threshold for clinically significant immune infertility.